1145 BAIL-OUT INTRAVASCULAR CORONARY LITHOTRIPSY FOR THE TREATMENT OF STENT IN-STENT UNDER EXPANSION. (15th December 2022) - Riverso, Vincenzo; Sorrentino, Sabato; Mongiardo, Annalisa; Polimeni, Alberto; Spaccarotella, Carmen; Calvelli, Pierangelo; Esposito, Giovanni; Indolfi, Ciro
Abstract: Background: in-stent restenosis remains a significant clinical problem for which optimal treatment is under debate. Intravascular lithotripsy (IVL) is mostly used for safe and effective treatment of de novo coronary calcifications, while the use of this technology to support bailout procedures, including stent under-expansion, is still off-label. One of the advantages of lithotripsy is the possible use after stent deployment. Case presentation: a 66-year-old male patient was admitted to our Institution due to a medically refractory angina and a coronary computed tomography (CCT) detecting three vessel disease with multiple critical stenosis. The patient had multiple comorbidities including history of hypertension, dyslipidemia, type 2 diabetes and multiple myocardial rivascularization. In 2003 he underwent coronary artery by-pass (CABG) with left internal mammal artery (LIMA) to left anterior descending (LAD) artery and free saphenous vein graft (VG) to the ramus intermedius (RI). In 2009 the patient underwent percutaneous coronary intervention (PCI) of the right coronary artery (RCA) with the implantation of a stent at the central segment, and a second stent at the crux cordis. For recurrent in-stent restenosis of the stent previously implanted at the central segment the patient was treated in 2013 with percutaneous balloon angioplasty (POBA) and in 2017 with the implantation of another drug eluting stent (Resolute Onyx, Medtronic, Santa Rosa, California) overlapping the proximal part of the scaffold. Coronary angiography revealed, a severe coronary artery disease with 80% stenosis of distal left main. The LAD was occluded at the middle segment and the ramus presented 99% stenosis at the proximal segment. The RCA had a diffuse severe in-stent restenosis involving the Resolute Onyx stent. Therefore, the operator decided to treat the restenosis with a direct stenting (Xience, Abbott Vascular Santa Clara, USA), but he was unaware of the fact that there was already an Onyx stent that was barely visible. After implantation, an inadequate expansion of the stents was observed (Figura 1A-B), which persisted despite post-dilation with non-compliant balloon (NCB) at high-pressure (Figure 1C). Given the persistence of stents under-expansion, it was decided to perform bail-out intravascular lithotripsy (IVL) therapy with a Shockwave balloon catheter (Figure 2A). The stent was then post-dilated with a NCB (Figure 2B). The final angiographic image and intravascular ultrasound (IVUS) showed an optimal stent expansion (Figure 3). Conclusion: intravascular lithotripsy could be used to treat undilatable stent-in-stent restenosis. Of interest, the case presented demonstrated, for the first time, the possible use of IVL in 2-stent layers, with an optima final stent expansion.